Binocular Coordination during Smartphone Reading in Esophoric Patients. Issue 1 (2nd January 2020) - Hirota, Masakazu; Morimoto, Takeshi; Miyoshi, Tomomitsu; Fujikado, Takashi
ABSTRACT: Purpose: To evaluate binocular coordination using video-oculography (VOG) during smartphone reading in patients with esophoria (EP) compared with control subjects. Patients and methods: Ten young and adult patients with EP (25.3 ± 7.3 years) and seven orthophoric or small-angle exophoric control subjects (25.7 ± 4.8 years) were examined. Eye movements were recorded during smartphone reading at 20, 30, and 50 cm using VOG. Differences in the horizontal fixation disparity at each distance between and within the groups were analyzed. Results: Horizontal esodeviation at 20 cm in the EP group (1.23° ± 2.00°) was significantly greater than that at 30 cm (−0.39° ± 0.73°; P = .027) and was significantly greater than horizontal exodeviation at 20 cm in the control group (−0.21° ± 0.17°; P < .001). Conclusion: The current findings suggest that the horizontal fixation disparities in the patients with EP deviate to eso-direction during smartphone use.